Physical Restraint in Adult Intensive Care Unit - Why and how are they used? (Bangladesh Critical Care Journal, 2016)
Background: Physical restraint is preferred practice in adult critical care to reduce the risk of injury and ensure patient safety. However, data on the extent of restraint practice intensive care unit is unknown in our setting to develop evidence based guidelines to promote the scientific use of this modalityMethods: This observational study was conducted for determining the prevalence, motives and ongoing practices of physical restraint. Data were collected from direct observation of physically restrained patients, review of patients record and from the nursing staff.Results: The results revealed that physical restraint was commonly used to prevent device dislodgment and to ensure patient safety. The results illustrated a lack of documentation on initiation and monitoring of use physical restraint.Conclusion: For a better care of patients, it is very important to develop a restraint policy for rational use of physical restrain respecting the patient autonomy and freedom.Bangladesh Crit Care J September 2016; 4 (2): 110-113